AN EFFECTIVE MEASURE OF CHILDHOOD ADVERSITY FOR USE WITH OLDER ADULTS. (11th November 2018) - Danielson, R; Sanders, G
Abstract: Background: Measures of childhood adversity (CA) have become a critical aspect to understanding health and quality-of-life outcomes across the lifespan. The literature offers few examples of the use of a measure of CA for older adults. The present study aimed to demonstrate a rationale for creating a CA index and its effectiveness for older adults using retrospective data from the Midlife in the United States (MIDUS) study (Ryff et al., 2016). Methods: Descriptive statistics, bivariate correlations, factor analysis, and hierarchical regression using MIDUS data from 2011–2014 collected through telephone interviews and follow-up mail questionnaires from older adults (N=1, 017 adults ages 55–76). Results: A CA index was created by summing 8 types of CA. The factor structure of the CA index was similar to the original ACE study. It had 2 factors comprising 4 items each: household dynamics and child abuse/neglect. The distribution of the individual CA types and the CA index created were consistent with findings from past studies of CA. The CA index demonstrated convergent validity in 2 outcomes previously shown to be related to CA – a negative association with life satisfaction and a positive association with comorbidity. The CA index provided more predictive value than either of the factors separately. Conclusions: This study demonstrated that an effective measure of cumulative CA could be created that would be of value to other studies using MIDUS data to study outcomes among older adults.